Analysis of the Transmission of SARS-CoV-2 Delta VOC in Yantai, China, August 2021 - Sun, Yulou; Zhang, Yuwei; Liu, Zimo; Li, Xia; Liu, Juan; Tian, Xinghan; Gao, Qiao; Niu, Peihua; Zhai, Hongli; Sun, Zhenlu; Tian, Yunlong; Wang, Ji (Frontiers in Medicine, 2022)
Objective Starting July 31, 2021, SARS-CoV-2 outbreak occurred in Yantai, Shandong Province. The investigation showed that this outbreak was closely related to the epidemic at Nanjing Lukou Airport. In view of the fact that there were many people involved in this outbreak and these people had a complex activity area, the transmission route cannot be analyzed by simple epidemiological investigation. Here we combined the SARS-COV-2 whole genome sequencing with epidemiology to determine the epidemic transmission route of Yantai. Methods Thirteen samples of SARS-CoV-2 outbreak cases from 31 July to 4 August 2021 were collected and identified by fluorescence quantitative PCR, then whole-genome deep sequencing based on NGS was performed, and the data were analyzed and processed by biological software. Results All sequences were over 29,000 bases in length and all belonged to B.1.617.2, which was the Delta strain. All sequences shared 2 amino acid deletions and 9 amino acid mutations in Spike protein compared with reference sequence NC_045512.2 (Wuhan virus strain). Compared with the sequence of Lukou Airport Delta strain, the homology was 99.99%. In order to confirm the transmission relationship between patients, we performed phylogenetic tree analysis. The results showed that the patient1 patient2 and patient9 belong to an independent branch, and other patients have a close relationship. Combined with the epidemiological investigation, we speculated that the epidemic of Yantai was transmitted by two routes at the same time. Based on this information, our prevention and control work was carried out in two ways and effectively prevented the further spread of this epidemic.